Термостійкість нанопорошків синтетичного алмазу детонаційного синтезу різних методів вилучення - Богатирьова, Г.П.; Забуга, В.Я.; Панова, А.М.; Цапюк, Г.Г.; Лисовенко, С.О.; Панов, О.В.; Бєда, О.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
In the given work influence of methods of reception nanopowder synthetic diamond of detonation synthesis on their thermostability is considered. It is determined, that the method of reception influences only an initial stage of oxidation. During oxidation of samples the quantity of little co-ordination atoms of carbon are decreases that results in reduction of a ratio СО2/СО/.